Being an Inclusive Faculty in New Zealand Schools - Renee Stewart (New Zealand Journal of Teachers' Work)
This article looks at the imperative to be an inclusive faculty, particularly where new immigrant teachers are concerned. It reviews the cultural, human, intellectual and social capital of schools and introduces the concept of teachers’ professional capital. The question of its transferability from one school to the next is then raised. In particular, the transferability of an immigrant teacher’s professional capital to the New Zealand context is explored. Teachers are urged to value the professional capital of all new colleagues so that inclusive attitudes and practices among staff will engender stronger professional networks.